2003
DOI: 10.1007/s11664-003-0088-0
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of emissivity of silicon-related materials and structures

Abstract: A brief review of the models that have been proposed in the literature to simulate the emissivity of silicon-related materials and structures is presented. The models discussed in this paper include ray tracing, numerical, phenomenological, and semi-quantitative approaches. A semi-empirical model, known as Multi-Rad, based on the matrix method of multilayers is used to evaluate the reflectance, transmittance, and emittance for (Hotliner), and separation by implantation of oxygen (SIMOX) wafers. The influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…In addition, the validity of this emissivity was confirmed from measurement of the Si substrate on a ceramic heater in the range of 100 to 700 • C at the same configuration in air. It was confirmed that the emissivity of Si was similar to the reported value (0.6 [20]), and the angle dependence was negligible. Furthermore, the measured sample temperature was not the temperature of the B implanted region.…”
Section: Copyright C 2016 the Institute Of Electronics Information Asupporting
confidence: 87%
“…In addition, the validity of this emissivity was confirmed from measurement of the Si substrate on a ceramic heater in the range of 100 to 700 • C at the same configuration in air. It was confirmed that the emissivity of Si was similar to the reported value (0.6 [20]), and the angle dependence was negligible. Furthermore, the measured sample temperature was not the temperature of the B implanted region.…”
Section: Copyright C 2016 the Institute Of Electronics Information Asupporting
confidence: 87%
“…Radiation from the exposed regions of the top surface is not considered, as the emissivity ε of polished silicon in the 3.7-5.1 μm wavelength is < 0.1 [32].…”
Section: Heat Balance Formulationmentioning
confidence: 99%
“…10 Two SiO 2 periods were found to give sufficiently high reflectivity at resonant wavelengths, owing to large contrast in indices of refraction. 11 An in-line array of 12 Si photoreceivers for optical interconnects was fabricated and operated with 40% (internal) quantum efficiency at 10 GHz and at wavelength λ ϭ 860 nm. Integration of the resonant cavity structure into a standard CMOS process flow could be challenging, as it requires special fabrication steps to form two buried SiO 2 layers in the silicon wafers and to grow device-quality epitaxial layer for the vertical p-i-n photodiodes.…”
Section: Si Photodetectorsmentioning
confidence: 99%
“…Infrared detector technologies employ several principles, including photovoltaics, photoconductors, Si and Ge devices, microbolometers, pyroelectrics, and micromechanics. For high-speed mid-IR devices (e.g., [8][9][10][11][12] µm, Ͼ10 10 Hz), inter-sub-band transitions in quantum well IR photodetectors (QWIPs) 3 are operated at cryogenic temperatures to suppress dark current or uncooled with heterodyne or photovoltaic detection. 4 At longer wavelengths, IR camera technologies are being adapted to extend their sensitivities beyond the IR into the terahertz region for see-through object detection, security, and defense applications.…”
Section: Introductionmentioning
confidence: 99%